2014
DOI: 10.1371/journal.ppat.1004433
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Antigen Driven Activation of CD14++CD16− Monocytes Is a Predictor of Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome

Abstract: Paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is an aberrant inflammatory response occurring in a subset of TB-HIV co-infected patients initiating anti-retroviral therapy (ART). Here, we examined monocyte activation by prospectively quantitating pro-inflammatory plasma markers and monocyte subsets in TB-HIV co-infected patients from a South Indian cohort at baseline and following ART initiation at the time of IRIS, or at equivalent time points in non-IRIS controls. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 48 publications
9
122
0
Order By: Relevance
“…Additionally, some control patients have rapid recovery of tuberculosisspecific T-cell function similar to TB-IRIS patients, but do not progress to IRIS [15][16][17]. In an exploratory analysis, we tested the hypothesis that increases in IL-6 levels, which have been associated with IRIS [11,13,15,20], would be less in control patients who also had rapid recovery of cellular immune function compared to TB-IRIS patients using previously determined IL-6 concentrations [15] and rank-sum tests. In this analysis, controls were restricted to those described in this study who had increases at week 4 of ART that were greater than the overall group median for IFN-γ + /IL-2 + /TNF-α + CD4 + T-cells, CD4 cell counts, and tuberculosis-specific IFN-γ responses by enzyme-linked immunospot (ELISpot) assay [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some control patients have rapid recovery of tuberculosisspecific T-cell function similar to TB-IRIS patients, but do not progress to IRIS [15][16][17]. In an exploratory analysis, we tested the hypothesis that increases in IL-6 levels, which have been associated with IRIS [11,13,15,20], would be less in control patients who also had rapid recovery of cellular immune function compared to TB-IRIS patients using previously determined IL-6 concentrations [15] and rank-sum tests. In this analysis, controls were restricted to those described in this study who had increases at week 4 of ART that were greater than the overall group median for IFN-γ + /IL-2 + /TNF-α + CD4 + T-cells, CD4 cell counts, and tuberculosis-specific IFN-γ responses by enzyme-linked immunospot (ELISpot) assay [15].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, innate immune responses involving rapid increases in proinflammatory cytokines such as interleukin 6 (IL-6) on ART have also been relatively consistently implicated in the pathogenesis of TB-IRIS [11,20].…”
mentioning
confidence: 99%
“…Prior studies have shown that the development of TB-IRIS is independently associated with expansion of CD14 ++ CD16 2 monocytes (22), which prompted us to investigate whether monocyte activation in TB-IRIS is associated with markers of inflammasome ++ monocyte subsets and compared data across the three clinical groups. We found that all these activation markers were increased to a variable degree in all three monocyte subpopulations across the three groups of patients, with CD64 expression showing consistent elevation in all three monocyte subsets.…”
Section: Expression Of Cd64 On Monocytes Was Associated With Monocytementioning
confidence: 99%
“…The reason why IRIS affects certain patients is not thoroughly understood, but may be linked to monocytederived responses [44] . Our expanding knowledge about human leukocyte antigens associations observed among non-seroconverting partners of HIV patients should uncover a role for genetic factors in the future [45] .…”
Section: Not Checkedmentioning
confidence: 99%